2011
DOI: 10.1080/09658211.2011.590504
|View full text |Cite
|
Sign up to set email alerts
|

Working memory in multilingual children: Is there a bilingual effect?

Abstract: This research investigates whether early childhood bilingualism affects working memory performance in 6-to 8-year-olds, followed over a longitudinal period of three years. The study tests the hypothesis that bilinguals might exhibit more efficient working memory abilities than monolinguals, potentially via the opportunity a bilingual environment provides to train cognitive control by combating interference and intrusions from the non-target language. Forty-four bilingual and monolingual children, matched on ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
111
1
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(133 citation statements)
references
References 50 publications
19
111
1
2
Order By: Relevance
“…The bilingual children were presumably disadvantaged on the L-S NWRT due to having less language-specific knowledge of Dutch to support memory representations needed to successfully repeat items from the L-S NWRT. This finding is consistent with previous work (Engel de Abreu et al, 2013;Engel de Abreu, 2011;Kohnert et al, 2006) and is also apparent in the scores on the language tests (see Table 2), which are substantially lower for the bilingual TD children than for their monolingual TD peers. Knowledge of Dutch did not appear to be as important for the Q-U NWRT as the two TD groups performed similarly.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The bilingual children were presumably disadvantaged on the L-S NWRT due to having less language-specific knowledge of Dutch to support memory representations needed to successfully repeat items from the L-S NWRT. This finding is consistent with previous work (Engel de Abreu et al, 2013;Engel de Abreu, 2011;Kohnert et al, 2006) and is also apparent in the scores on the language tests (see Table 2), which are substantially lower for the bilingual TD children than for their monolingual TD peers. Knowledge of Dutch did not appear to be as important for the Q-U NWRT as the two TD groups performed similarly.…”
Section: Discussionsupporting
confidence: 82%
“…Their study also included a group of monolingual children with LI and the diagnostic power of the measure was not sufficient to separate the bilingual TD children from the children with LI. Second, Engel de Abreu (2011) found no differences between monolingual and bilingual TD children on working memory tasks, but did find group effects on the NWRT with higher scores in the monolingual group. The effect disappeared when vocabulary was controlled which suggests that performance on a NWRT relies on language-specific lexical knowledge.…”
Section: Nwrts With Bilingual Children: Potential Pitfallsmentioning
confidence: 93%
“…Our findings are consistent with those reported by Morales et al (2013) and , but differ from those reported by Engel de Abreu and colleagues (Engel de Abreu, 2011;Engel de Abreu et al, 2012). We are confident that the differences between our findings and those reported by Engel de Abreu are not down to task differences as we used the same tasks from the AWMA as Engel de Abreu.…”
Section: Discussionsupporting
confidence: 76%
“…This is noteworthy, given that some studies have shown that bilingualism confers an advantage on working memory tasks (Sorge, Toplak, & Bialystok, 2017; Veenstra et al, 2016). However, the relationship between bilingualism and better working memory performance has not been consistently demonstrated (Engel De Abreu, 2011; Gathercole et al, 2014; Loe & Feldman, 2016). …”
Section: Discussionmentioning
confidence: 99%